Análise química, microestrutural, determinação das propriedades mecânicas e dureza de ligas odontológicas (Ag Pd,Co Cr e NiCr) fundidas em diferentes temperaturas - Olivieri, Karina Andrea Novaes [UNESP] (2000)
The metal restorations are used in Dentistry since /ast ce11tury. Nowadays we have resources that can to get castings more accurate, with news materiais and equipments and techniques more precises continue to be introduced with regularity in the scientific area. The purpose of this study was evaluates the metallurgical aspects of the dental alloys when they were submitted to different castings temperatures. To each alloy, Wiron 99- Rego (NiCr), Wironit- Bego (CoCr) and Palliag M- Degussa (AgPd), were cast, with lost wax technique, 20 specimens, separeted in two groups of 10 each one, in two different casting temperatures: a) in accordance with the manufactures' instructions (T1); b) above manufactures' instructions (T2). It was done chemical and metallographic ana!ysis wich optical microscope in the alloys in these conditions: no cast, T1 and T2. It was determined mechanical properties and hardness (T1 and T2). The microstructures were similar to no cast, T1 and T2, but T1 was few better than T2. The results didn't show significantly differences statistics to chemical analysis and to mechanical properties. The hardness were larger in T1 and T2 than no cast